A repercussão geral no Supremo Tribunal Federal - Coelho, Damares Medina (2014)
This paper analyses Brazilian Supreme Federal Court s ( Supremo Tribunal Federal , STF) decision behavior, under the specific perspective of the general repercussion of the constitutional question. The starting point was the academic debate and several empiric studies regarding the judicial decision making process in the supreme courts. The Brazilian experience was analyzed using a comprehensive empiric research that comprised the examination of the whole universe of general repercussion s topics judged by STF until December 31st 2013. We have investigated how STF has been applying the institute of general repercussion in order to understand general repercussion effects on the access to constitutional jurisdiction. The outcome evidenced the rapporteur power over the definition of general repercussion s result, as well as his selectivity of the case, of the process to be judged and of the judging house. We have identified that the institutional context influences the trial s output, once the virtual plenary is the main competent house for judging general repercussion on STF. The analysis showed that, despite virtual plenary success and its adjustment to general repercussion trial, there are limitations to be faced for its improvement and a possible amplification of its competences. Finally, we concluded that the incorporation of the general repercussion of the constitutional question to STF s decision process increased access to constitutional jurisdiction.